Direct two-photon excitation of Sm3+, Eu3+, Tb3+, Tb.DOTA(-), and Tb.propargylDO3A in solution - Sorensen, T; Blackburn, O; Tropiano, M; Faulkner, S (2012)
We have observed direct two-photon excitation of samarium, europium and terbium ions in solution upon near IR excitation using a tuneable pulsed light source, and have also studied two-photon processes in a pair of related terbium complexes, namely [Tb.DOTA] - and Tb.propargylDO3A. Direct two-photon excitation of lanthanides is observed in simple systems in the absence of sensitizing chromophores. Where even simple chromophores such as a triple bond are present in the complex, then single and two-photon excitation of chromophore excited states competes with direct two-photon excitation of the ions and is the dominant pathway for sensitizing formation of the lanthanide excited state. © 2012 Elsevier B.V. All rights reserved.